Evaluation of an education and follow‐up programme for implantable cardioverter defibrillator‐implanted patients. Issue 17 (3rd April 2013) - Cinar, Fatma I; Tosun, Nuran; Kose, Sedat
<x xml:space="preserve">Abstract</x> Aims and objectives To determine the experiences, problems and the need for care and education of implantable cardioverter defibrillator‐implanted patients and to assess the effects of an education and nurse follow‐up programme on their quality of life, anxiety, depression and knowledge level. Background Although implantable cardioverter defibrillator has become a well‐established therapy for people experiencing potentially lethal dysrhythmias, implantable cardioverter defibrillator patients may have physical and psychosocial problems due to the implantation. Applying a planning education and follow‐up programme to implantable cardioverter defibrillator‐implanted patients may prevent the need for more intensive treatment during the postimplantation period. Design A mixed methods design that used both qualitative and quantitative data collections and analysis was used for this study. Methods The study was performed in the cardiology department in Turkey between 2009–2010. The data were collected using the 'Semi‐Structured Interview Form', 'Form for Assessment of Patients' Knowledge Level about implantable cardioverter defibrillator', 'Spielberger's State‐Trait Anxiety Inventory', 'Beck Depression Inventory II' and 'The Short‐Form 36 Health Survey'. All forms were completed at the beginning of the study and at six months. The study included 27 patients in the experimental group and 27 patients in the control group. Results The results showed that the patients were living with various physical and psychosocial problems and insufficient knowledge regarding the implantable cardioverter defibrillator. Education and follow‐up programme increased knowledge levels, decreased anxiety and depression scores and improved several subscales of quality of life in the experimental group patients. Conclusion It was recommended that education and follow‐up programme be used for patients scheduled to undergo implantable cardioverter defibrillator implantation, starting before implantation and continuing thereafter, to help patients adapt to a life with implantable cardioverter defibrillator. Relevance to clinical practice Planned education and follow‐up programme conducted by nurses may improve the knowledge levels and quality of life, anxiety and depression scores of the implantable cardioverter defibrillator‐implanted patients.